Analysis The Effect of Service Quality Supply Chain Management Healthcare Product Towards Hospital and Clinical Laboratories Satisfaction - Devi Suryani; Nurmala Nurmala (PT Mattawang Mediatama Solution, 2024)
Supply chain management (SCM) is one of the critical things in healthcare sector because it has a direct effect on the quality of services provided. The aim of this study is to analyse the effect of service quality on supply chain management of healthcare products in hospital and clinical laboratories satisfaction. The study adapted six dimensions of service quality namely assurance, communication, empathy, reliability, responsiveness, and tangibles. Survey data was analysed using Structural Equation Modelling-Partial Least Square (SEM-PLS). A total of 67 hospitals and clinical laboratories were the research sample. The results show that service quality on supply chain management of healthcare product has a positive effect on hospital and clinical laboratories satisfaction. Reliability is the most prominent dimension that determines hospital and clinical laboratory satisfaction. Items that contribute to reliability include complaint handling, product authenticity guarantee, order processing, on time delivery, providing product information updated and routine visitation.